2021
DOI: 10.3389/fpsyg.2021.626118
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual Variation Refuses to Go Away: A Bayesian Computer Model of Language Change in Communicative Networks

Abstract: Treating the speech communities as homogeneous entities is not an accurate representation of reality, as it misses some of the complexities of linguistic interactions. Inter-individual variation and multiple types of biases are ubiquitous in speech communities, regardless of their size. This variation is often neglected due to the assumption that “majority rules,” and that the emerging language of the community will override any such biases by forcing the individuals to overcome their own biases, or risk havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 90 publications
(139 reference statements)
3
9
0
Order By: Relevance
“…While in the prior study, we defined centrality as betweenness centrality, we complemented these results here by exploring whether various other node-level metrics (local clustering coefficient, node degree, eigenvector centrality, and closeness centrality) might exert different influences. These findings, available only in the Supplementary Materials (see Part 3.4), not only expand upon but also validate the results presented by Josserand et al (2021).…”
Section: The Network: Types and Metricssupporting
confidence: 87%
See 3 more Smart Citations
“…While in the prior study, we defined centrality as betweenness centrality, we complemented these results here by exploring whether various other node-level metrics (local clustering coefficient, node degree, eigenvector centrality, and closeness centrality) might exert different influences. These findings, available only in the Supplementary Materials (see Part 3.4), not only expand upon but also validate the results presented by Josserand et al (2021).…”
Section: The Network: Types and Metricssupporting
confidence: 87%
“…Previous studies (see fig. 13 in Josserand et al, 2021) have shown that in a type of Bayesian model of language change similar to the ones implemented here but where the linguistic feature was binary, language stabilized before 1000 rounds in all network types (see our Supplementary Materials, Part 3.1 for visualization). Here, we introduced a conservative margin and analyzed the inter and intraindividual variability after 3000 rounds (when all agents had produced 3000 utterances) in order to make sure that language would have stabilized.…”
Section: Measurementsmentioning
confidence: 79%
See 2 more Smart Citations
“…It should be emphasized that the model presented and analysed in this paper is concerned with only one potential external ("environmental") predictor of contact-induced change, namely the proportion of L2 speakers in a speech community. Other possible external factors conditioning language change have been considered in the literature, ranging from population size (Lupyan & Dale 2010;Nettle 2012;Koplenig 2019) to social network geometries (Ke & Gong & Wang 2008;Fagyal et al 2010;Kauhanen 2017;Josserand et al 2021) or combinations of such parameters (Trudgill 2004). Although the present model sets such effects aside, this is not to deny their importance.…”
Section: Introductionmentioning
confidence: 99%